Parametric study on impact behaviour of sisal and cenosphere reinforced natural rubber-based hybrid composites: FE approach. (2021) - Rajkumar, Dasari; Mahesh, Vishwas; Joladarashi, Sharnappa; Kulkarni, S.M.
Abstract: This paper aims to study the impact analysis of sisal fiber and cenosphere filler reinforced natural rubber composite using commercially available finite element software. The proposed green composite is studied for impact behaviour by varying the weight percentage of the cenosphere filler particles in a natural rubber sheet. Composite is modelled with stacking sequence sisal-rubber-sisal using finite element software and impacted by three different rigid impactors (Conical, Hemi-spherical and Flat) at the velocity of 8 m/s. Modelling and simulation of this proposed composite laminate are solved using the explicit dynamic solver of Abaqus Computer-Aided Engineering Finite Element Modelling. The results of the low-velocity impact of the proposed green composite with sisal-rubber-sisal stacking sequence exhibit better energy absorption by varying the weight percentage of the Cenosphere. Also, the energy absorbed by laminate was more for the Conical impactor than the Hemi-spherical and Flat impactors and the extent of damage is more when impacted by the Flat impactor due to its larger contact area.